2016
DOI: 10.1038/srep26679
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MiRNA-211 suppresses cell proliferation, migration and invasion by targeting SPARC in human hepatocellular carcinoma

Abstract: Previous studies have shown that the expression of miR-211 was downregulated in hepatocellular carcinoma (HCC). However, the molecular function and mechanism of miR-211 in HCC growth and invasion are largely unclear. We found that miR-211 is downregulated in HCC tissues and cell lines, respectively. Further results showed that low miR-211 associated with TNM stage, vein invasion status, and poor prognosis. Ectopic expression of miR-211 effectively suppressed HCC cell proliferation, migration and invasion both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 30 publications
(40 reference statements)
2
30
0
Order By: Relevance
“…The secreted protein acidic and rich in cysteine (SPARC; alternative names: osteonectin; ON or basement membrane-40; BM-40) family is recognized as extracellular matrix proteins[6]. A differential expression of SPARC in tumor tissue and its surrounding stroma compared to normal tissues has been reported for many different types of cancer[7].…”
Section: Introductionmentioning
confidence: 99%
“…The secreted protein acidic and rich in cysteine (SPARC; alternative names: osteonectin; ON or basement membrane-40; BM-40) family is recognized as extracellular matrix proteins[6]. A differential expression of SPARC in tumor tissue and its surrounding stroma compared to normal tissues has been reported for many different types of cancer[7].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, SPARC acts as a tumor suppressor to inhibit migration and invasion of breast cancer cells and inhibits tumor growth and angiogenesis in neuroblastoma . However, SPARC has also been reported to act as a tumor promotor that is closely related to cell adhesion, migration, metastasis, poor prognosis, and remodeling . In our study, we examined subcutaneous tumor formation in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…10,33 However, SPARC has also been reported to act as a tumor promotor that is closely related to cell adhesion, migration, metastasis, poor prognosis, and remodeling. [34][35][36] In our study, we examined subcutaneous tumor formation in nude mice. We found that tumor size in SPARCoverexpressing tumors was larger than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…SPARC was reported to be involved in prostate cancer migration into bone and promoted glioma cell motility and invasion . SPARC contributed to the migration and invasion of human hepatocellular carcinoma . By decreasing type IV collagen levels, SPARC promoted cell invasion in vivo .…”
Section: Discussionmentioning
confidence: 99%